Opposite effects of a glucokinase activator and metformin on glucose‐regulated gene expression in hepatocytes. Issue 8 (10th April 2017) - Al‐Oanzi, Ziad H.; Fountana, Sophia; Moonira, Tabassum; Tudhope, Susan J.; Petrie, John L.; Alshawi, Ahmed; Patman, Gillian; Arden, Catherine; Reeves, Helen L.; Agius, Loranne
Abstract : Aim: Small molecule activators of glucokinase (GKAs) have been explored extensively as potential anti‐hyperglycaemic drugs for type 2 diabetes (T2D). Several GKAs were remarkably effective in lowering blood glucose during early therapy but then lost their glycaemic efficacy chronically during clinical trials. Materials and Methods: We used rat hepatocytes to test the hypothesis that GKAs raise hepatocyte glucose 6‐phosphate (G6P, the glucokinase product) and down‐stream metabolites with consequent repression of the liver glucokinase gene ( Gck ). We compared a GKA with metformin, the most widely prescribed drug for T2D. Results: Treatment of hepatocytes with 25 mM glucose raised cell G6P, concomitantly with Gck repression and induction of G6pc (glucose 6‐phosphatase) and Pklr (pyruvate kinase). A GKA mimicked high glucose by raising G6P and fructose‐2, 6‐bisphosphate, a regulatory metabolite, causing a left‐shift in glucose responsiveness on gene regulation. Fructose, like the GKA, repressed Gck but modestly induced G6pc . 2‐Deoxyglucose, which is phosphorylated by glucokinase but not further metabolized caused Gck repression but not G6pc induction, implicating the glucokinase product in Gck repression. Metformin counteracted the effect of high glucose on the elevated G6P and fructose 2, 6‐bisphosphate and on Gck repression, recruitment of Mlx‐ChREBP to the G6pc and Pklr promoters and induction of these genes. Conclusions: Elevation in hepatocyte G6P and downstream metabolites, with consequent liver Gck repression, is a potential contributing mechanism to the loss of GKA efficacy during chronic therapy. Cell metformin loads within the therapeutic range attenuate the effect of high glucose on G6P and on glucose‐regulated gene expression.